Aktivitas Fisik, Asupan Serat dan Status Ekonomi dengan Kejadian Obesitas pada Remaja di SMP Negeri 11 Kota Banjarmasin - Nida Wati; Malisa Ariani; Umi Hanik Fetriyah (Universitas Malahayati Lampung, 2023)
ABSTRACT One of the problems of nutrition and poor nutrition in adolescents is obesity. Obesity can occur in infants, children, adolescents, adults and the elderly. Obesity can cause diseases such as cardiovascular disease, diabetes mellitus, osteoarthritis and even death. Several factors that influence the occurrence of obesity are physical activity, nutritional intake (fiber), economic factors. To determine the relationship between physical activity, fiber intake and economic status with the incidence of obesity in adolescents at SMPN 11 Banjarmasin City. Quantitative research with observational analytic cross sectional design. The sample of this study amounted to 209 adolescents. The sampling technique in this research is random sampling. Collecting data using a questionnaire, measuring height with a microtoise and weight with a digital scale. Data analysis using Chi Square test. Adolescents who are obese are 23 people (11.0%), some teenagers have inactive physical activity with obesity of 12.2%, fiber intake is not as recommended with obesity of 11.1% and high economic status with obesity of 12, 8%. The relationship between physical activity and the incidence of obesity (p = 0.422), the relationship between fiber intake and the incidence of obesity (p = 1,000), economic status and the incidence of obesity (p = 0.432). There is no relationship between physical activity, fiber intake and economic status with the incidence of obesity in adolescents at SMPN 11 Banjarmasin. Parents are expected to encourage motivation or invite children to do physical exercise by exercising 3-5 times a week. Organize meals in a day such as reducing fast food and eating foods that are high in fiber and low in calories and can calculate pocket money with children's needs at school. Keywords: Economic Status, Fiber Intake, Obesity, Physical Activity, Teenager ABSTRAK Salah satu permasalahan gizi dan nutrisi yang kurang baik pada remaja adalah obesitas. Obesitas bisa terjadi pada bayi, anak-anak, remaja, dewasa serta lanjut usia. Obesitas dapat menyebabkan penyakit seperti kardiovaskuler, diabetes mellitus, osteoartritis hingga kematian. Beberapa faktor yang memengaruhi terjadinya obesitas yaitu aktivitas fisik, asupan gizi (serat), faktor ekonomi. Mengetahui adanya hubungan aktivitas fisik, asupan serat dan status ekonomi dengan kejadian obesitas pada remaja di SMPN 11 Kota Banjarmasin. Penelitian kuantitatif dengan analitik observasional desain cross sectional. Sampel penelitian ini berjumlah 209 remaja. Pengumpulan data menggunakan kuesioner, pengukuran tinggi badan dengan microtoise dan berat badan dengan timbangan digital. Analisis data menggunakan uji Chi Square. Remaja yang mengalami obesitas sebanyak 23 orang (11,0%), sebagian remaja memiliki aktivitas fisik tidak aktif dengan obesitas sebesar 12,2%, asupan serat tidak sesuai anjuran dengan obesitas sebesar 11,1% dan status ekonomi tinggi dengan obesitas sebesar 12,8%. Hubungan aktivitas fisik dengan kejadian obesitas (p = 0,422), hubungan asupan serat dengan kejadian obesitas (p = 1,000), status ekonomi dengan kejadian obesitas (p = 0,432). Tidak ada hubungan aktivitas fisik, asupan serat dan status ekonomi dengan kejadian obesitas pada remaja di SMPN 11 Banjarmasin. Orang tua diharapkan mendorong untuk menumbuhkan motivasi atau mengajak anak latihan fisik dengan berolahraga 3-5x dalam seminggu. Mengatur makanan dalam sehari seperti mengurangi makanan cepat saji dan mengonsumsi makanan yang tinggi serat rendah kalori serta dapat memperhitungkan uang saku dengan keperluan anak di sekolah. Kata Kunci: Aktivitas Fisik, Asupan Serat, Obesitas, Remaja, Status Ekonomi